2008
DOI: 10.1089/cap.2007.0121
|View full text |Cite
|
Sign up to set email alerts
|

Medication Effects on Symptoms of Attention-Deficit/Hyperactivity Disorder in Children with Fetal Alcohol Spectrum Disorder

Abstract: Pharmacologic treatment of acute stress disorder (ASD) is a novel area of investigation across all age groups. Very few clinical drug trials have been reported in children and adolescents diagnosed with ASD. Most of the available, potentially relevant, data are from studies of adults with posttraumatic stress disorder (PTSD). The atypical antipsychotic agents have been reported to be effective as an adjunctive treatment for adults with PTSD. There have been a limited number of studies published regarding atypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 26 publications
1
49
0
1
Order By: Relevance
“…This was the premise for a few clinical studies using psychostimulant drugs like Dextroamphetamine and Methylphenidate for FASD, especially in cases of FASD and symptoms of hyperactivity and inattention. O'Malley et al [8], Doig et al [17], Infante et al [31], Snyder et al [20], and Oesterheld et al [28] reported clinical studies to delineate the best stimulant therapy for FASD with symptoms of hyperactivity and inattention. The outcomes of these studies gave mixed yet uncertain verdicts for the use of these psychostimulants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was the premise for a few clinical studies using psychostimulant drugs like Dextroamphetamine and Methylphenidate for FASD, especially in cases of FASD and symptoms of hyperactivity and inattention. O'Malley et al [8], Doig et al [17], Infante et al [31], Snyder et al [20], and Oesterheld et al [28] reported clinical studies to delineate the best stimulant therapy for FASD with symptoms of hyperactivity and inattention. The outcomes of these studies gave mixed yet uncertain verdicts for the use of these psychostimulants.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of these studies gave mixed yet uncertain verdicts for the use of these psychostimulants. In these studies, inattention was found to respond better to Dextroamphetamine than Methylphenidate, but a high adverse event profile induced discontinuation [17,28]. Dextroamphetamine was deduced as preferred given its action on the D1 receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a significant number of the trials (approximately one third) had to be stopped due to concerns regarding negative side effects. Most recently, Doig et al [2008] reviewed 41 medication trials in a sample of 27 children diagnosed with an FASD and ADHD. The majority of the trials consisted of stimulant medications, although some included combinations of psychostimulants with other medications, such as clonidine, risperidone, or carbamazepine, Significant effects were seen on all three domains of the MTA-SNAP-IV, although more children received normalized scores in the hyperactive/ impulsive and oppositional/defiant domains than in the inattentive domain.…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…Both of these studies with medication and FASD were limited by very small sample sizes that impacts power and generalizability, as well as insufficient information on dosing and medication compliance. Doig et al [52] examined the effects of medication on ADHD symptoms in a larger sample (n=27) of children (aged 5 to 14 years) with FASD and found that children with FASD tended to showed more normalized scores on teacher-rated hyperactivity/impulsivity and opposition/defiance than inattention, indicating a different pattern of response than is reported for otherwise typically developing children.…”
Section: Medical Interventionsmentioning
confidence: 99%